The Analysis of Dairy Farming Efficiency in East Java: Evidence Post The Foot and Mouth Disease Outbreak - Alla Asmara; Yeti Lis Purnamadewi; Wiwiek Rindayanti; Muhammad Nur Faaiz Achsani; Asaduddin Abdullah; Naufal Fadhillah; Tiara Anisa Fitri (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Foot and Mouth Disease is a highly contagious disease in livestock that can cause great economic losses when there is an outbreak of the disease.Purpose: This study examines the characteristics and dynamics of milk production on smallholder farms in East Java after the outbreak of foot and mouth diseaseDesign/methodology/approach: The regencies of Malang and Pasuruan are the research locations because they are the centers of milk production in East Java. To obtain a representative sample, farmer households were disaggregated by farm location, with a total of 93 farmer households surveyed 45 from Malang Regency and 48 from Pasuruan Regency. East Java Province was recorded to have 282.364 dairy cows in 2022, accounting for 56% of the national dairy cattle population, making it the key region in dairy cattle production. Through a comparative analysis of key factors, such as feed management, labor efficiency, and animal composition, the study revealed significant differences in milk production between the two regions.Findings/Result: The study found that the number of lactating cows positively impacted milk production, with farmers in both Malang and Pasuruan effectively optimizing concentrate feed. However, labor management challenges in Pasuruan hindered full resource utilization, highlighting the need for improved labor practices. To sustain dairy farming in East Java, tailored strategies that address regional differences, optimize resources, enhance labor quality, and invest in disease prevention and farmer education are essential for increasing productivity and resilience. Conclusion: Policy implications highlight the need for targeted training programs, improved measures to prevent the spread of foot and mouth disease (FMD), and better access to veterinary services to support farmers in adapting to FMD. Ultimately, strengthening resilience in the dairy farming sector is critical to ensuring the sustainability and productivity of dairy farming in East Java.Originality/value (State of the art): This study provides novel insights by not only analyzing the dynamics of milk production in these regions post-FMD but also by examining the specific factors affecting recovery, such as feed management, labor efficiency, and animal composition. This study offers a comparative analysis between the two major dairy-producing areas in East Java. Keywords: dairy farming, foot and mouth disease, milk production, lactating cow, resource management